A Caged Lanthanide Complex as a Paramagnetic Shift Agent for Protein NMR - Prudêncio, Miguel; Rohovec, Jan; Peters, Joop A.; Tocheva, Elitza; Boulanger, Martin J.; Murphy, Michael E. P.; Hupkes, Hermen-Jan; Kosters, Walter; Impagliazzo, Antonietta; Ubbink, Marcellus (Chemistry : a European journal, 2004)
A lanthanide complex, named CLaNP (caged lanthanide NMR probe) has been developed for the characterisation of proteins by paramagnetic NMR spectroscopy. The probe consists of a lanthanide chelated by a derivative of DTPA (diethylenetriaminepentaacetic acid) with two thiol reactive functional groups. The CLaNP molecule is attached to a protein by two engineered, surface‐exposed, Cys residues in a bidentate manner. This drastically limits the dynamics of the metal relative to the protein and enables measurements of pseudocontact shifts. NMR spectroscopy experiments on a diamagnetic control and the crystal structure of the probe‐protein complex demonstrate that the protein structure is not affected by probe attachment. The probe is able to induce pseudocontact shifts to at least 40 Å from the metal and causes residual dipolar couplings due to alignment at a high magnetic field. The molecule exists in several isomeric forms with different paramagnetic tensors; this provides a fast way to obtain long‐range distance restraints. The paramagnetic CLaNP molecule: A lanthanide complex (CLaNP; caged lanthanide NMR probe) was developed for the characterisation of proteins by paramagnetic NMR spectroscopy. This probe can be specifically attached to Cys residues on the surface of a protein and causes pseudocontact shifts up to 40 Å away from the metal ion (see picture).